Sustainable pathways in Indonesia's palm oil industry through historical institutionalism - Annisa Joviani Astari; Jon C. Lovett; Meditya Wasesa (World Development Sustainability)
This study investigates the evolution of sustainable palm oil policies in Indonesia through a historical institutionalism framework, tracing the influence of both domestic institutional developments and global dynamics on the sustainability trajectory of the palm oil sector, focusing on the Indonesian Sustainable Palm Oil (ISPO) initiative. Employing longitudinal content analysis, this research examines institutional frameworks from 1957 to 2022, identifying patterns of institutional continuity and change, as well as how path dependency and critical junctures have shaped policy development. Utilizing a combination of primary and secondary data—including thirteen interviews, seven archived interview videos, four focus group discussions, and 143 document archives—this analysis thematically codes qualitative data to uncover key themes related to institutional change and sustainability pathways. Findings reveal that the institutionalization of sustainable palm oil in Indonesia is shaped by both exogenous and endogenous dynamics; international pressures and the emergence of global sustainability networks have prompted shifts in national institutional arrangements, while domestic political forces and commitments to reduce greenhouse gas emissions have facilitated gradual institutional transformations. The ISPO certification embodies these changes, reflecting a synthesis of existing regulations and illustrating the path-dependent nature of sustainability policies. This research contributes to the literature on institutional change and offers insights for policymakers aiming to design effective strategies that stimulate sustainable practices in the palm oil industry.